The acceptance and effectiveness of telecommuting (work from home) in Malaysia - Teh, Boon Heng; Ong, Tze San; Loh, Yin Lee (Sri Krishna International Research & Educational Academic Consortium, 2012)
Telecommuting/Telework or “Work from Home” is slogan that we hear over the times almost everywhere in the world especially in developed nation. According to WorldatWork,an international association for human resource professionals and business leaders based in USA, the key finding of Telecommuting are as follows:Workers Increasingly Working from Anywhere, Employers Are Expanding Teleworking opportunities, Number of "At Least Once Per Year" Teleworkers Remains Steady, Frequency of Teleworking is Growing, Broadband Use Rises Sharply for Home Based Teleworkers, Teleworkers Are Far More Prevalent Users of Wireless.